Pengaruh E-Learning Terhadap Hasil Belajar Jawa Siswa Kelas IV SD Negeri 1 Sugihan Jatirogo Tuban - Alawiyah, Sukma Wibawati; Anggraeni, Sri Prastiti Kusuma (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2021)
This study aimed to analyze the effect of e-learning on the learning outcomes of fourth grade Javanese script students at SD Negeri Sugihan Jatirogo Tuban. This study used an experimental method with the research design was the control group pretest-posttest design, namely experimental research conducted on two groups of classes. In implementing this study, students were given a pretest. Then, after being given a different treatment between the controller class and the experimental class, a posttest was carried out. The test given was in the form of multiple choice test. In addition to the test, there were also supporting data in the form of interview questionnaires for the parents of fourth grade students. The results obtained that the posttest average score of the experimental class students was (80,96), that showed it was increased significantly compared to before receiving treatment (51,68). This study concluded the effect of learning on the learning outcomes of fourth grade Javanese script students at SD Negeri 1 Sugihan Jatirogo Tuban. The learning obstacle of e-learning based at SD N 1 Sugihan, Jatirogo, Tuban was inadequate internet network facilities.